1981
DOI: 10.1152/ajpendo.1981.240.2.e184
|View full text |Cite
|
Sign up to set email alerts
|

Insulin binding and sensitivity in rat skeletal muscle: effect of starvation

Abstract: In contrast to adipose tissue and heart, the in vitro sensitivity of skeletal muscle to insulin is enhanced by starvation. To determine the basis for this, insulin binding and its ability to stimulate glucose metabolism were examined in the incubated rat soleus. In solei from 50-g rats, starvation for 48 h enhanced insulin binding by 50-100% at concentrations of 100 ng/ml or less. Starvation also resulted in higher basal and insulin-stimulated rates of glycogen synthesis, glycolysis, and glucose uptake. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

1982
1982
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 3 publications
5
36
0
1
Order By: Relevance
“…Supporting this view, we have observed that, in heart and skeletal muscle from diabetic rats, a fall in GLUT-4 protein content coincides with a decreased effect of insulin stimulating glucose transport [4,[6][7][8]. However, our study also reveals that this is not a general finding, and, whereas the effect of insulin on glucose utilization is increased in skeletal muscle during fasting [12][13][14][15], this is concomitant with either unaltered or even decreased GLUT-4 protein levels. In this regard, it should be kept in mind that insulin action relies not only on the content of cellular GLUT-4 but also on the biological activities of the insulin receptor, as well as on several post-receptor events distal to the glucose carrier itself.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Supporting this view, we have observed that, in heart and skeletal muscle from diabetic rats, a fall in GLUT-4 protein content coincides with a decreased effect of insulin stimulating glucose transport [4,[6][7][8]. However, our study also reveals that this is not a general finding, and, whereas the effect of insulin on glucose utilization is increased in skeletal muscle during fasting [12][13][14][15], this is concomitant with either unaltered or even decreased GLUT-4 protein levels. In this regard, it should be kept in mind that insulin action relies not only on the content of cellular GLUT-4 but also on the biological activities of the insulin receptor, as well as on several post-receptor events distal to the glucose carrier itself.…”
Section: Discussionsupporting
confidence: 72%
“…In this regard, it should be kept in mind that insulin action relies not only on the content of cellular GLUT-4 but also on the biological activities of the insulin receptor, as well as on several post-receptor events distal to the glucose carrier itself. In this regard, it should be mentioned that streptozotocininduced diabetes leads to a marked impairment of tyrosine receptor kinase activity in skeletal muscle [51], and that fasting enhances insulin binding as assessed in the incubated muscle preparation [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the hindquarter preparation consists of a mixture of red and white muscle fibres (Maizels, Ruderman, Goodman & Lau, 1977) while the rat soleus is composed primarily of slow-twitch, oxidative, red muscle fibres (Ariano, Armstrong & Edgerton, 1973), may have some bearing on the difference in response of ATP to fasting in the two preparations. Also, it has recently been suggested that there may be intrinsic differences between perfused and incubated muscles and that comparison of data obtained with these two preparations may be questionable (Brady, Goodman, Kalish & Ruderman, 1981).…”
Section: Implications For Diabetes Therapymentioning
confidence: 99%
“…In vitro, insulin responsiveness was also impaired in liver (Cech et al, 1980), but not in muscle (Brady et al, 1981 Thus, in Reddy, 1979;Herrera et al, 1981;Brady et al, 1981;Le Marchand-Brustel & Freychet, 1979). These increases correlated with the decrease in plasma insulin generally observed in fasted rats (Penicaud et al, 1985).…”
Section: Introductionmentioning
confidence: 96%